THE ROLE OF SONGS IN PROMOTING VOCABULARY LEARNING AMONG YOUNG EFL STUDENTS IN ELEMENTARY SCHOOL - Farah Nadia; Fauziah Fauziah; Farizawati Farizawati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jabal Ghafur, 2026)
This study investigates the role of songs in promoting vocabulary learning among young EFL students in elementary school. Using a quasi-experimental design, this research involved two classes: an experimental class that learned using songs and a control class that learned using conventional methods. Data were collected through pretests and posttests using vocabulary bingo cards, as well as documentation analysis through classroom observations and visual records to support the learning outcomes. The results showed that students in the experimental class achieved significantly higher vocabulary scores compared to the control class. The use of songs not only helped students remember vocabulary more effectively but also increased their learning enthusiasm, active participation, and confidence in using English. Documentation analysis confirmed that students in the experimental class were more engaged, active, and responsive during the learning process. These findings suggest that integrating songs into English learning can be an effective strategy to enhance vocabulary acquisition and student engagement in EFL classrooms.Keywords: EFL classrooms; elementary students; songs; vocabulary learning; vocabulary mastery.